(untitled) (The Review of Diabetic Studies, 2024)
Oral cancer remains a significant global health burden, characterized by high morbidity and mortality rates largely attributable to delayed diagnosis and inconsistent implementation of preventive and biosafety measures across healthcare settings. Despite advances in diagnostic technologies and increased awareness of oral potentially malignant disorders, early detection rates remain suboptimal, particularly in low- and middle-income regions and within fragmented healthcare systems. Dental settings represent a critical frontline opportunity for early identification of oral malignancies; however, the effectiveness of screening is highly dependent on coordinated teamwork, strict biosafety practices, and efficient laboratory diagnostic pathways. This comprehensive review explores the multifaceted roles of dentists, dental assistants, sterilization technicians, and laboratory services in enhancing early oral cancer detection while maintaining high standards of infection prevention and biosafety. Emphasis is placed on clinical screening protocols, risk stratification, interprofessional communication, sterilization workflows, specimen handling, and histopathological confirmation. By synthesizing current evidence, international guidelines, and multidisciplinary models of care, this review proposes an integrated framework aimed at improving diagnostic timeliness, reducing occupational and patient exposure risks, and strengthening health system resilience. The findings underscore that early oral cancer detection is not solely a clinical task but a system-level responsibility requiring seamless collaboration across dental and laboratory services.